Numerical analysis of the double suction centrifugal pump with different tongue shape. (July 2018) - Yan, S N; Luo, X Q; Zhang, L F; Li, C H
Abstract: The paper deals with the influence of the tongue shape on the flow characteristics at the near-tongue region of the volute in the double suction centrifugal pump with long-tongue, middle-tongue and short-tongue respectively. For this study, the computational fluid domains including suction chamber, impeller and volute was simulated by means of the commercial CFD software that solved the Navier-Stokes equations for three-dimensional steady flow. The results show that the tongue shape has a significant impact on the pump head and efficiency in a range of 0.4Qd -1.4Qd flow rate. Under small flow conditions, the head and efficiency of the short-tongue model are higher than that of the middle-tongue model and long-tongue model. Under large flow conditions, the head and efficiency curves of the three models are relatively close. In addition, the tongue shape has a great influence on the pressure and the streamline distribution in the near-tongue region. Therefore, effectively changing the tongue shape can improve the internal flow pattern of the double suction centrifugal pump and reduce the pressure pulsations. The tongue shape also has a great influence on the turbulent kinetic energy distribution. By changing the tongue shape the numerical value of the turbulent kinetic energy can be effectively reduced, thus the generation of the turbulent vortex and the energy loss of the pump will be reduced. It is shown that the tongue shape has a great influence on the performance of the double suction centrifugal pump. This study has certain reference value to improve the pressure pulsation of the double suction centrifugal pump.